Evaluation of The Implementation of The Getting Zero To Halinar (Handphone, Pungli, Narkoba) Programm in The Correctional Institutions of The Class I Cipinang Jakarta - Indra Jaya Ali; R. Madhakomala; Corry Yohana (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
The aims of this study is to evaluate the implementation and regulations and legal policies regarding the